REKAYASA SYSTEM TEKNOLOGI SEMI KONTINYU UNTUK PEMBUATAN BIO-DIESEL DARI MINYAK JARAK DAN CPO - Hasmawaty AR; Erna Yuliwati; Renilaili; M Ali (KINETIKA, 2013)
One of the alternative for fosil replacing is biodisel which is produced from standard material like palm oil and sawit mentah. From the BPPT experiment, excessise biodisel has octan number to the piston machine, free sulfur, and produce a minimum smoke. So that, it is necessary to have methode due to a biodisel productcessary to have methode due to a biodisel production from CPO and jarak oil, in order to make manufacturing process in an eficient way. It is con an eficient way. It is considered that we hnsidered that we have to design biodisel manufacturing technology system continuously, which produced biodisel convertion higher. The experiment uses a standard material from PT PN VII. A standard material that fulfill the SNI. The result of biodisel redemen comparison analysis,with batch process, and produced 70% in spce, 82% in CPO. The next process from jarak oil produced 89% and 93% from CPO.